The converging impact of tuberculosis, AIDS, and food insecurity in Zambia and South Africa - Bond, Virginia; Chileshe, Mutale; Magazi, Busisiwe; Sullivan, Clare (International Food Policy Research Institute, 2008)
Zambia and South Africa (SA) are two countries that are seriously affected by the dual epidemics of tuberculosis (TB) and HIV. While both are attempting to integrate public TB and HIV services to reach co-infected people, there is little evidence on how the synergy of co-infection with TB and HIV plays out for affected families in the context of poverty and overstretched public services. An anthropological study carried out in 2006/7 documented the social and economic impact of TB, HIV, and food insecurity on poor households in rural Zambia and peri-urban SA. Anthropological research was conducted in 18 households affected by TB throughout the period of TB treatment and in 17 comparative non-affected households.